2016
DOI: 10.2147/ijn.s90850
|View full text |Cite
|
Sign up to set email alerts
|

Potential antitumor activity of novel DODAC/PHO-S liposomes

Abstract: In recent studies, we showed that synthetic phosphoethanolamine (PHO-S) has a great potential for inducing cell death in several tumor cell lines without damage to normal cells. However, its cytotoxic effect and selectivity against tumor cells could increase with encapsulation in cationic liposomes, such as dioctadecyldimethylammonium chloride (DODAC), due to electrostatic interactions between these liposomes and tumor cell membranes. Our aim was to use cationic liposomes to deliver PHO-S and to furthermore ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
(68 reference statements)
0
18
0
7
Order By: Relevance
“…Recently, the PHO-S was encapsulated in DODAC liposomes by our research group, aiming to maximize the antitumor effect and providing a greater availability of PHO-S in the tumour microenvironment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, the PHO-S was encapsulated in DODAC liposomes by our research group, aiming to maximize the antitumor effect and providing a greater availability of PHO-S in the tumour microenvironment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates the efficacy of liposomal formulation DODAC/PHO-S to promote B16F10 cell death. Recently, these liposomes were evaluated on normal and did not promote significant cell death [ 4 ]. Studies have shown that the use of nanocarriers are promising drug delivery systems, presenting several advantages such as low skin irritation and increased protection of the encapsulated drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations